The Effect of Alcoholic Extract of Citrullus Colocynthis on The Structural Manifestations of The Parasite Fasciola Gigantica and Its Comparison With The Drug Pendazole - Ali Mutlak Nawar; Wissam Malik Dawood; Nagham Yassin Kadhem (Universitas Muhammadiyah Sidoarjo, 2024)
The current study aims to find out the effect of alcoholic extracts of the fruit of the Citrullus colocynthis plant, as it was during the current study during the period from 12/2/2022 to 24/4/2023 and by 206 livers for cows, including (31) infected livers and 1348 livers for sheep that did not show infection. In the current study, the incidence of giant liver Fasciola gigantica cows was 15.04%, while sheep hadn't infection during the study period. The results of the current study show that there are different effects in the tissues of the treated worms if compared to the control group, which was showing the integrity of the tissues well after 6 hours, as it is observed the layers of the body wall, spines and muscle layers that cover the wall, as well as the parenchyma tissue in which the body systems are embedded, which did not notice any changes in those tissues and structures, which include (for intestinal backfilling, testicles, mules and uterus). As noted, the damages vary according to the concentration of separation and deformation in the longitudinal and circular muscles, and a few cells are seen in the tenderloin. The thorns are still present in the cover, and the effect of the drug albendazole is little practical Clearly.